PREPARING STUDENTS FOR THE USE OF THEATER ACTIVITIES FOR CHILDREN’S DEVELOPMENT SOFT SKILLS: EUROPEAN CONTEXT - Demchenko, Olena; Kazmirchuk, Natalia; Zhovnych, Olesia; Stakhova, Inna; Podorozhnyi, Vadym; Baranovska, Iryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The article substantiates the importance of introducing European experience in the training of future teachers in Ukrainian higher education institutions. Features of preparation of future teachers for realization of theatrical activity in work with children are opened, attention is focused on social and educational value of theater for development of the general and special abilities of children. The functions realized by theatrical activity in the process of soft skills development of children of primary school age are singled out. The article emphasizes the various forms and types of theatrical activities and ways of organizing them with children (from creating a theatrical character or a specific image to its interpretation and display on the stage).The purpose of the publication is to present the experience of the higher education institution of Ukraine in preparing future primary school teachers for the use of theater activities for children`s development soft skills taking into account the European context.In the research the results of diagnostics of primary school teachers on the use of theatrical activities in their own pedagogical practice are presented. The results of monitoring the awareness of future primary school teachers with the theoretical and methodological principles of using theatrical activities as a means of developing soft skills in primary school children and their level of readiness to organize theatrical activities with children are demonstrated. The experience of teachers of Ukrainian pedagogical universities in the implementation of European innovative technologies and practices in lectures and practical classes is demonstrated. The article reveals the content of preparing students for the use of European experience in the organization of theatrical activities in the education of children, offers guidelines.